Answer:
Step-by-step explanation:
(b - 4)(3b - 1) is the factored form of some second degree polynomial. Once you factor to this point, you can solve for the values of b using the Zero Product Property, which says that one of the those factors has to equal 0 for the product to equal 0 (cuz any number times 0 is equal to 0). The first expression is b - 4. If we set b - 4 equal to 0, we can solve for b:
b - 4 = 0 so
b = 4
Likewise with the second factor, 3b - 1. Set it equal to 0 and solve for b:
3b - 1 = 0 and
3b = 1 so
b = 1/3